2004
DOI: 10.1002/eji.200324278
|View full text |Cite
|
Sign up to set email alerts
|

Expression and function of 4‐1BB during CD4 versus CD8 T cell responses in vivo

Abstract: 4-1BBL -/-mice have a defect in recall CD8 + T cell responses to viruses, whereas CD4 + T cell responses to virus are unimpaired in these mice. In contrast, both CD4 + and CD8 + T cells respond to 4-1BB ligand (4-1BBL) in vitro. To clarify the role of 4-1BB/4-1BBL in CD4 + versus CD8 + T cell responses in vivo, we compared CD4 (OT-II) and CD8 (OT-I) TCR transgenic T cells responding to the same antigen in an in vivo adoptive transfer model in 4-1BBL +/+ versus 4-1BBL -/-mice. During primary and secondary respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
83
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 44 publications
(51 reference statements)
9
83
0
Order By: Relevance
“…[34,50,[54][55][56][57][58]. In addition, recent reports using TCR transgenic mice show a positive role of CD137 in CD4 + T cell activation in vivo [59,60]. Further work in defined in vivo systems of antigen-specific CD4 + T cells is needed to clarify these discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…[34,50,[54][55][56][57][58]. In addition, recent reports using TCR transgenic mice show a positive role of CD137 in CD4 + T cell activation in vivo [59,60]. Further work in defined in vivo systems of antigen-specific CD4 + T cells is needed to clarify these discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…We selected the TNFR superfamily members CD27 and 4-1BB as targets, because both are known to influence the CD8 T cell response. CD27 is expressed constitutively on naive CD8 T cells, whereas 4-1BB is induced within 24 h of T cell activation in vivo (10,11). Studies using CD27 or 4-1BB ligand (4-1BBL)-deficient mice demonstrated a nonredundant contribution by both receptors to the accumulation of influenza virus-specific CD8 T cells during the primary response and the formation and response of memory cells (12,13).…”
mentioning
confidence: 99%
“…Evidence that 4-1BB can play a role early in the response comes from systemic administration of agonist anti-4-1BB Abs, which can enhance initial antitumor and antiviral T cell responses with greater effects on CD8 compared with CD4 T cells (20 -24). However, studies in 4-1BB ligand (4-1BBL)4 -deficient mice showed that 4-1BBL was dispensable for primary responses to nonreplicating Ags or to influenza virus delivered via a minimally infectious systemic route (19,25). Under these conditions, 4-1BBL was found to control the magnitude of the recall response to influenza virus (25), later attributed to a role for 4-1BBL in maintaining CD8 T cell survival in the weeks after initial infection (26).…”
mentioning
confidence: 99%